Complete sequence of Cynanchum rostellatum (Apocynaceae: Asclepiadoideae) chloroplast genome and its phylogenetic analysis. Issue 7 (3rd July 2022) - Pei, Lixin; Shu, Shengnan; Ji, Baoyu; Cui, Ning
Abstract: Cynanchum rostellatum (Turcz.) Liede and Khanum 2016 is a perennial herbaceous twining vine that is widely distributed in Japan, South Korea, the United States of America, and China. In this study, the complete chloroplast (cp) genome of C. rostellatum was sequenced using the Illumina platform and assembled for the first time. This plastome has a circular structure with a length of 160, 641 bp. The GC content of the plastome was 37.82%. The cp genome contained 113 unique genes, including 79 protein-coding, 30 transfer RNA, and four ribosomal RNA genes. Phylogenetic analysis based on the complete cp genome sequences of the Asclepiadoideae subfamily showed that C. rostellatum was closely related to C. bungei in the genus Cynanchum . These results provide useful information for both phylogenetic research and the utilization of C. rostellatum .